PENGARUH PERBEDAAN DOSIS PELET TEPUNG DAUN KELOR TERHADAP PERTUMBUHAN, KELULUSHIDUPAN, DAN HISTOLOGI USUS DALAM PEMBERIAN PAKAN IKAN NILA (Oreochromis niloticus) - Gunawan, Sahrul; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
This purpose of this study was to determine the best dose and the effect of moringa leaf pellets on the growth, survival, and intestinal histology of tilapia (Oreochromis niloticus). The research was conducted in January-March 2025 at the Cultivation Laboratory of the Faculty of Marine and Fisheries, Udayana University, and the Denpasar Veterinary Center. The method used was a Completely Randomized Design (CRD) with 4 treatments and 3 replications, using Moringa leaf pellet doses as follows: A (0%), B (25%), C (50%), and D (75%). Parameters observed included absolute weight and length growth, survival rate, feed conversion ratio (FCR), intestinal villus length, and water quality. The results showed no significant differences (P>0.05) in growth, survival, or FCR among treatments. However, intestinal villus length differed significantly (P<0.05). Water quality parameters during the study were within the limits set by Government Regulation of the Republic of Indonesia No. 22 of 2020, temperature ranging from 27.4–27.5 ℃, dissolved oxygen (DO) from 6.7–6.8 mg/L, pH from 8.10–8.17, and ammonia levels below 0.50 mg/L.